Predictors of Executive Functions in Preschoolers: Findings From the SPLASHY Study - Zysset, Annina E.; Kakebeeke, Tanja H.; Messerli-Bürgy, Nadine; Meyer, Andrea H.; Stülb, Kerstin; Leeger-Aschmann, Claudia S.; Schmutz, Einat A.; Arhab, Amar; Puder, Jardena J.; Kriemler, Susi; Munsch, Simone; Jenni, Oskar G. (Frontiers in Psychology, 2018)
Executive functions have been reported to play a crucial role in children’s development, affecting their academic achievement, health, and quality of life. This study examined individual and interpersonal predictors for executive functions in 555 typically developing preschool children aged two to six years. Children were recruited from 84 child care centers in the German- and French-speaking parts of Switzerland within the Swiss Preschoolers’ Health Study (SPLASHY). A total of 21 potential predictors were assessed at the first measurement (T1). These included nine demographic/biological predictors, such as socioeconomic status, preterm birth, physical activity, and motor skills; six psychological predictors, such as hyperactivity, cognitive functioning, and emotionality; and six interpersonal predictors, such as parenting style and stress, presence of siblings, and days spent in the child care center. The predictive value of these variables on executive functions one year later (T2) was assessed using both standard multiple regression analysis and penalized regression to avoid overfitting due to the number of potential predictors. Female sex (β = .14), socio-economic status (β =.14), fine motor skills (β = .17), cognitive functions at T1 (β = .15), and executive functions at T1 (β = .30) were all associated with executive functions at T2, exhibiting small to medium effect sizes. All predictors together accounted for 36% of the variability in executive functions. However, none of the interpersonal predictors were significant. Thus, we conclude that most of the factors that can predict executive functions in preschool age are individual variables, and these tend to be more difficult to influence than interpersonal factors. In fact, children from families with low socio-economic status may be particularly vulnerable to poor executive functions. Furthermore, encouraging fine motor skills and cognitive functioning early in life may support the development of executive functions.